Rencontres, en présence et à distance, avec Jacques Perriault - Georges-Louis Baron (Centre National d'Enseignement à Distance, 2022)
During the course of a professional career, we meet dozens of people whose ideas have made us think and progress, either immediately or afterwards because ideas take time to mature. For me, Jacques Perriault is undoubtedly one of them. The first meeting occurred in the late 1970s. Then others took place, mostly at a distance, also in the field of what was then called educational computing. In the following text, I will recall some elements of context and then analyze synthetically what seems to me to be his scientific contribution, long after our meetings. I will focus on the period before 2000, before his integration into the field of information and communication sciences (ICS).